CXC Chemokine Ligand 10 DNA Vaccination Plus Complete Freund’s Adjuvant Reverses Hyperglycemia in Non-Obese Diabetic Mice (The Review of Diabetic Studies, 2023)
OBJECTIVE: Complete Freund’s Adjuvant (CFA) is known to arrest autoimmune diabetes development in non-obese diabetic (NOD) mice. However, CFA alone cannot induce effective remission in diabetic NOD mice. Previously, we reported that anti-CXC chemokine ligand 10 (CXCL10) antibody can promote beta-cell proliferation in NOD mice. In the present study, we aimed to examine whether anti-CXCL10 plus CFA treatment can effectively reverse autoimmune diabetes development. METHODS: Systemic supply of antiCXCL10 antibody by CXCL10 DNA vaccination in combination with CFA injection was performed in new-onset diabetic NOD mice. Remission rate of diabetes, histological characteristics of residual insulitis lesions, residual beta-cell mass, and regulatory T cell population in local pancreas were examined. RESULTS: A high frequency of diabetes reversal was observed after combination treatment with anti-CXCL10 plus CFA. In mice showing diabetes reversal, residual betacell mass was significantly increased, and some beta-cells were in a proliferative state. Although systemic cytokine profiles were unaffected, the frequency of “hybrid regulatory T cells”, i.e. regulatory T cells expressing CXCR3, was significantly increased in local pancreatic lesions. This was possibly associated with the regulation of anti-islet autoimmunity. CONCLUSIONS: Anti-CXCL10 plus appropriate immune adjuvant therapy arrested, and reversed, type 1 diabetes development.